Cornelis van de Linde. Builder for the trading company Nederlandsche Handel-Maatschappij (NHM) (Bulletin KNOB, 2020)
After his education as an architect Cornelis van de Linde, a farmer's son from the province of Zeeland (* 1886), became office manager in the employment of K.RC. De Bazel. The latter was highly respected as some kind of spiritual representative of his colleagues. He was a leader to Van de Linde as well, although he remained level-headed (typical for a native of Zeeland) with respect to De Bazel's theosophical meditations.De Bazel had the supervision of the design of the principal building of the Nederlandsche Handel-Maatschappij (NHM) in Amsterdam, but Van de Linde played an important part in its construction. After the death of De Bazel in 1923 he completed the building to the full satisfaction of the client. Subsequently, in 1928 he and his partner A.P. Smits were commissioned for the design of the principal building (trading station) of the Nederlandsche Handel-Maatschappij in Batavia, then Dutch East Indies.A first design still had De Bazel characteristics. but the final design was explicitly aimed at functional requirements and at the building conditions on site. The new building had a monumental layout. with one principal wing and two side wings around a large courtyard. The construction took more than three years and was supervised by Van de Linde. For this purpose mid 1929 he moved to Batavia, the present Jakarta, with his family. During this period he also built a new establishment for NHM in Medan, which was completed in 1932. Construction and detail drawings were for the greater part made in Amsterdam.In these years the edge of the old city centre of Batavia was revitalized with large urban developments, such as a new railway station. The new trading station was situated quite prominently opposite this railway station. Although a bank should have a representative appearance, it was especially the construction. availability of materials and climatic conditions that determined the design.Keeping out the sunlight and the tropical heat took high priority. For this purpose a well-shaded gallery surrounded the building. Ventilation was applied in hollow floors. The construction of reinforced concrete was covered with plastered brick. Clients have access to the large hall by way of the main entrance and the staircase. The stairwell is dominated by stained-glass windows of F.H. Abbing extending over two floors. When comparing the trading station in Batavia and the NHM building in Amsterdam, the functional clarity of the former and the monumental weight of the latter are striking.In Batavia an open horizontal-looking building, in Amsterdam a vertical and closed one. In Batavia daylight came from two sides, in Amsterdam a large amount of daylight came in through a lightwell. Similarities between the two buildings, on the other hand. are to be found in the finishing of the interior. such as the use of Venetian tiles, marble for the counters and quite Spartan looking furniture for the personnel.